Redox state of Earth’s magma ocean and its Venus-like early atmosphere - Sossi, Paolo A. (Sci Adv, 2020)
Exchange between a magma ocean and vapor produced Earth’s earliest atmosphere. Its speciation depends on the oxygen fugacity (fO(2)) set by the Fe(3+)/Fe(2+) ratio of the magma ocean at its surface. Here, we establish the relationship between fO(2) and Fe(3+)/Fe(2+) in quenched liquids of silicate Earth-like composition at 2173 K and 1 bar. Mantle-derived rocks have Fe(3+)/(Fe(3+)+Fe(2+)) = 0.037 ± 0.005, at which the magma ocean defines an fO(2) 0.5 log units above the iron-wüstite buffer. At this fO(2), the solubilities of H-C-N-O species in the magma ocean produce a CO-rich atmosphere. Cooling and condensation of H(2)O would have led to a prebiotic terrestrial atmosphere composed of CO(2)-N(2), in proportions and at pressures akin to those observed on Venus. Present-day differences between Earth’s atmosphere and those of her planetary neighbors result from Earth’s heliocentric location and mass, which allowed geologically long-lived oceans, in-turn facilitating CO(2) drawdown and, eventually, the development of life.